2013
DOI: 10.1161/atvbaha.112.300154
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Coronary Thrombosis in Cigarette Smoke Exposure

Abstract: Abstract-Acute rupture or erosion of a coronary atheromatous plaque and subsequent coronary artery thrombosis cause the majority of sudden cardiac deaths and myocardial infarctions. Cigarette smoking is a major risk factor for acute coronary thrombosis. Indeed, a majority of sudden cardiac deaths attributable to acute thrombosis are in cigarette smokers. Both active and passive cigarette smoke exposure seem to increase the risk of coronary thrombosis and myocardial infarctions. Cigarette smoke exposure seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
2
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 118 publications
7
132
2
12
Order By: Relevance
“…Moreover, our data revealed that the e‐cigarette–exposed platelets are less sensitive to inhibition by PGI 2 , in comparison to those from clean air; which may have also contributed to the thrombosis phenotype in these mice. Importantly, these results are also “similar” to those observed with traditional tobacco smoke, which heightens platelet activation (eg, aggregation)17, 94 and renders platelets less sensitive to PGI 2. 95 On the other hand, we observed no difference in the activation state of leukocytes between e‐cigarettes and clean air.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, our data revealed that the e‐cigarette–exposed platelets are less sensitive to inhibition by PGI 2 , in comparison to those from clean air; which may have also contributed to the thrombosis phenotype in these mice. Importantly, these results are also “similar” to those observed with traditional tobacco smoke, which heightens platelet activation (eg, aggregation)17, 94 and renders platelets less sensitive to PGI 2. 95 On the other hand, we observed no difference in the activation state of leukocytes between e‐cigarettes and clean air.…”
Section: Discussionsupporting
confidence: 65%
“…After “validating” our model, we first sought to investigate the impact of e‐cigarettes on thrombogenesis, as it is the major cause of tobacco‐induced CVD,38 including thrombosis‐based diseases 17, 77, 78, 79, 80, 81, 82, 83. Our findings revealed, for the first time, a drastic reduction in the time for carotid artery occlusion, indicating a prothrombotic phenotype, even after only a week of whole‐body exposure to e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking elevates the expression of soluble adhesion molecules, vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) in ECs. Exposure to cigarette smoke increased intraplaque inflammation and neovascularization, which leads to intraplaque hemorrhage and consequent necrotic core formation (160). Nicotine affects serum thromboxanes A2/B2 and catecholamines, which enhance platelet activation (12).…”
Section: Smokingmentioning
confidence: 99%
“…Cigarette smoking is a well-established modifiable risk factor for atherosclerotic coronary artery disease (CAD) [1][2][3]. It is known for its role in impairing endogenous fibrinolysis, enhancing platelet aggregation and thrombus formation, and promoting the development of a thin fibrous cap in atherosclerotic coronary plaques, thus predisposing the plaque to erosion and subsequent thrombosis leading to acute coronary syndrome (ACS) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%